Gendering Public Diplomacy: Turkey and Europe in the 1930s. Issue 2 (4th March 2023) - Rumelili, Bahar; Aydın-Düzgit, Senem; Gülmez, Seçkin Barış
ABSTRACT: This article scrutinizes the role of women's rights and women actors in Turkey's public diplomacy strategy in the 1930s and discusses whether and if so how it managed to change the long-standing European prejudices against Turkey. Accordingly, first, the article discusses the early reforms of the Turkish Republic and their European reception. Then, relying on critical discourse analysis, it examines two prominent cases; namely, Keriman Halis' victory in the 'Miss Universe' beauty contest in 1932 and the organization of the 12 th Congress of the International Alliance of Women in Istanbul in 1935, comparatively to observe how they resonated in Europe. The article will conclude by assessing whether the changing status of women in Turkish society has played a role in shifting the European perceptions of the newly established Turkish Republic.